A new species of Neorhadinorhynchus (Acanthocephala: Cavisomidae) from Platax teira (Ephippidae) from Iraqi marine waters. Issue 1 (2nd January 2016) - Smales, Lesley R.; Al-Hasson, Hayder A. H.; Al-Niaeem, Khalidah S.; Al-Azizz, Suzan A.
ABSTRACT: A new species of Neorhadinorhynchus (Acanthocephala: Cavisomidae), N. basrahiensis, is described from the small intestine of the longfin batfish Platax teira Forsskål, 1775, from Iraqi marine waters. The new species is distinguished from its congeners by the proboscis armature of 12 rows of 8–10 hooks, the largest hooks being up to a third larger than the largest hooks previously described for the genus. It is first record of the genus in the Ephippidae and from Iraqi marine waters; the fourth species of the genus Neorhadinorhynchus to be described from the Indian Ocean.